Na/K-ATPase Gene Expression in the Human Cochlea: A Study Using mRNA in situ Hybridization and Super-Resolution Structured Illumination Microscopy - Liu, Wei; Rask-Andersen, Helge (Frontiers in Molecular Neuroscience, 2022)
Background The pervasive Na/K-ATPase pump is highly expressed in the human cochlea and is involved in the generation of the endocochlear potential as well as auditory nerve signaling and relay. Its distribution, molecular organization and gene regulation are essential to establish to better understand inner ear function and disease. Here, we analyzed the expression and distribution of the ATP1A1, ATP1B1, and ATP1A3 gene transcripts encoding the Na/K-ATPase α1, α3, and β1 isoforms in different domains of the human cochlea using RNA in situ hybridization. Materials and Methods Archival paraformaldehyde-fixed sections derived from surgically obtained human cochleae were used to label single mRNA gene transcripts using the highly sensitive multiplex RNAscope® technique. Localization of gene transcripts was performed by super-resolution structured illumination microscopy (SR-SIM) using fluorescent-tagged probes. GJB6 encoding of the protein connexin30 served as an additional control. Results Single mRNA gene transcripts were seen as brightly stained puncta. Positive and negative controls verified the specificity of the labeling. ATP1A1 and ATP1B1 gene transcripts were demonstrated in the organ of Corti, including the hair and supporting cells. In the stria vascularis, these transcripts were solely expressed in the marginal cells. A large number of ATP1B1 gene transcripts were found in the spiral ganglion cell soma, outer sulcus, root cells, and type II fibrocytes. The ATP1B1 and ATP1A3 gene transcripts were rarely detected in axons. Discussion Surgically obtained inner ear tissue can be used to identify single mRNA gene transcripts using high-resolution fluorescence microscopy after prompt formaldehyde fixation and chelate decalcification. A large number of Na/K-ATPase gene transcripts were localized in selected areas of the cochlear wall epithelium, fibrocyte networks, and spiral ganglion, confirming the enzyme’s essential role for human cochlear function.